2010
DOI: 10.1063/1.3437043
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic detection efficiency of superconducting nanowire single-photon detectors with different thicknesses

Abstract: We evaluate experimentally the intrinsic detection efficiency (IDE) of superconducting NbN nanowire single-photon detectors in the range of wire thicknesses from 4 to 12 nm. The study is performed in the broad spectral interval between near-ultraviolet (wavelength 400 nm) and near-infrared (wavelength 2000 nm) light with plane waves at normal incidence. For visible light the IDE of the thinnest detectors reaches 70%. We use numerically computed absorptance of the nanowire-structures for the analysis of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 40 publications
11
106
3
Order By: Relevance
“…Later in 2010, single-vortex hopping was proposed as the detection mechanism beyond the threshold [23], and in 2011, it was suggested that vortices are responsible for all detection events, including those at high currents in the plateau of the detection efficiency [63]. In this model, the arrival of the photon decreases the entry barrier for vortices as discussed in section 3, which enables a vortex crossing or makes it at least more likely.…”
Section: Photon-triggered Vortex-entry Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Later in 2010, single-vortex hopping was proposed as the detection mechanism beyond the threshold [23], and in 2011, it was suggested that vortices are responsible for all detection events, including those at high currents in the plateau of the detection efficiency [63]. In this model, the arrival of the photon decreases the entry barrier for vortices as discussed in section 3, which enables a vortex crossing or makes it at least more likely.…”
Section: Photon-triggered Vortex-entry Modelmentioning
confidence: 99%
“…A higher bias current corresponds to a larger cut-off wavelength or a lower minimum photon energy E min [23] and also a smaller jitter [24]. The limit for I b is an experimentally measured I c which in turn cannot exceed the depairing critical current I c,dep .…”
Section: Stationary State Of Snspdmentioning
confidence: 99%
See 1 more Smart Citation
“…In this "plateau region," nearly every absorbed photon triggers the formation of a normal conducting domain 15 leading to an intrinsic detection efficiency (IDE) approaching 100%. 16,17 The device detection efficiency (DDE) is the product of photon absorptance (ABS) of the meander and IDE: DDE ¼ ABS Â IDE. ABS itself depends on the absorptance of the thin superconducting film and geometric effects, such as the meander filling factor or a polarization dependent absorptance 18 and is limited to Շ20% for a bare meander.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [7] and references therein). Superconducting fluctuations, e.g., excitation of superconducting vortices [8][9][10][11][12], have been put forward as an explanation.…”
mentioning
confidence: 99%